2022
DOI: 10.3390/ijms232012180
|View full text |Cite
|
Sign up to set email alerts
|

Association between Insertion-Deletion Polymorphism of the Angiotensin-Converting Enzyme Gene and Treatment Response to Antipsychotic Medications: A Study of Antipsychotic-Naïve First-Episode Psychosis Patients and Nonadherent Chronic Psychosis Patients

Abstract: We investigated whether a functional insertion/deletion (I/D) polymorphism of angiotensin-converting enzyme (ACE) influenced antipsychotic treatment. At baseline, and after 8 weeks of treatment with various antipsychotic medications, we assessed patients’ Positive and Negative Syndrome Scale (PANSS) scores, PANSS factors, and metabolic-syndrome-related parameters (fasting plasma lipid and glucose levels, and body mass index). A total of 186 antipsychotic-naïve first-episode psychosis patients or nonadherent ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Abouelfath et al [44,45] highlighted the etiological role of ACE I/D polymorphisms in MetS and its components progress, additionally, DD polymorphism and D allele were shown to be protective against MetS development among adult Moroccan population and in Chilean subjects. In an Indonesian study, the frequent polymorphism among patients with DM type II was the DD variant and no association was found between ACE I/D polymorphisms and MetS & its related parameters [46,47]. This discrepancy in the results regarding the distribution frequency of ACE I/D gene polymorphisms, alleles and their participation in the development in DM type II, MetS and its related components could be attributed the ethnic variations among different population.…”
Section: Discussionmentioning
confidence: 99%
“…Abouelfath et al [44,45] highlighted the etiological role of ACE I/D polymorphisms in MetS and its components progress, additionally, DD polymorphism and D allele were shown to be protective against MetS development among adult Moroccan population and in Chilean subjects. In an Indonesian study, the frequent polymorphism among patients with DM type II was the DD variant and no association was found between ACE I/D polymorphisms and MetS & its related parameters [46,47]. This discrepancy in the results regarding the distribution frequency of ACE I/D gene polymorphisms, alleles and their participation in the development in DM type II, MetS and its related components could be attributed the ethnic variations among different population.…”
Section: Discussionmentioning
confidence: 99%
“…For antipsychotic‐naïve first episode psychosis patients, an increase in ACE activity was also seen after 2 months of treatment with atypical antipsychotic risperidone compared to pre‐treatment, but only for the D/D genotype subgroup (Nani, Dal Mas, et al, 2020). In such drug‐naïve first episode psychosis patients, the D/D genotype was associated with reduced psychopathology symptoms, as assessed using the Positive and Negative Syndrome Scale (PANSS) scores, with patients with I/D or D/D also showing a greater reduction in a range of symptoms following antipsychotic medication (Nadalin et al, 2022). Conversely, other studies have also found evidence that carrying at least one D‐allele provides protection against SCZ, either generally (Crescenti et al, 2009) or specifically in women (Mazaheri & Saadat, 2015), while this polymorphism was not associated with SCZ in a Croatian population, but with a significant impact of the polymorphism on the clinical expression of the illness (Nadalin et al, 2012).…”
Section: Ace and Ace2 In Disorders Of The Brainmentioning
confidence: 99%